POLA PERTUMBUHAN DAN SERAPAN HARA Echinacea purpurea - MONO RAHARDJO; SUDIARTO SUDIARTO; ROSITA SMD; SUKARMAN SUKARMAN (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
Growth pattern and nutrient uptake of Echinacea purpureaEchinacea purpurea or purple cone flower, belongs lo Aslcraceac family which grown naturally in Noth America. The plant known as is Ihe number one Immune herbs in the world, since it has a greal potential lor improving and developing leukocyte cell activity. Recently, Echinacea has been evalualcd/tcsled as adjuvant in cancer therapy, AIDS and chronic exhaustion. Echinacea purpurea is more potential for immunity improvement lhan those of other herbal medicine. Therefore, the study on its growlh rale, growth pattern, and nutrient uptake in a new tropical environmental condition is very important in order lo suppot its cultivation technology, lo identify the growth pattern, growlh rale, nutrient uptake, and simplisia quality. A ield trial had been conducted in Cipanas at 1 100 m above sea level (asl) in 1999-2000. Plot size was 4x3 m, and plant spacing was 50 x 40 cm. Ten samples was taken from each growth stage of the plants. The growth stages were (I) vegetative I (VI) at I month alter planting (map), (2) vegetative 2 (V2) al 1 .5 map, (3) generative I (Gl) at 2 0 map, (4) generative 2 (G2) at 2.5 map. (5) generative 3 (G3) at 3.0 map. and (6) generative 4 (G4) al 3.5 map. The results of the research showed thai growth rate, nutrient uptake of N, P. K. Mg. and S linearly increased in line with Ihe increase of plan! ages The highest dry weight accumulation was found on aerial part of plant (slem I leal), and the lowest was occurred on root pat. The amount of dry weight accumulation was 75.72 g/plnul. and nutrient uptake oIN, P. K.Ca, Mg, and S. respective!) was 1529.1. 1 40.01. 1943.25, 654.59. 358.66. and 88.57 mg/plant.